Residential care for serious and chronic mentally ill persons in Mini- Residences - Javier Sánchez Alfonso (Fundación para el Desarrollo de la Enfermería, 2009)
Following the process of Psychiatric Reform it has become necessary to have alternative housing and residential care for the serious and chronic mentally ill people. The problems and needs of these people are numerous and complex and include both aspects such as psychiatric or healthy and psychosocial aspects. We will base this study in the Mini-Residences, which are a clear example of European development regarding to residential centres where they focus on resources integrated into the community, and reflects the principles of the General Health Law.Objective: To determine the characteristics of the social or health care provided to the mentally ill persons in the Mini-Residential (MR), and describe both beneficial aspects and potential weaknesses.Sites: 4 Mini Residences in the south area of the Community of MadridTarget population: This is the people who are included under the term "Chronic Mentally ill persons" hospitalised in the four Mini Residential described before. Taken together, these mini-Residences have 108 places of care, a total of 415 places along the whole Community of Madrid.Design: The qualitative study, using techniques such as review and documental analysis, participative observation, personal and semi-structured interviews, drafting proposals and a final poll.Data Analysis: This will be conducted through the creation of codes, categories and subcategories. For the analysis process the tool ATLAS-Ti will be used as a common way to support the text analysis.